Highmountain region of the mountains: Jablanica, Galicica and Pelister - Kolčakovski, Dragan (Macedonian Journal of Ecology and Environment, 1994)
The analyzing of the mountains by their altitude's belt have a considerable scientific (learned) and practical (applicable) significance. Researching the mountain's belt, we can get appreciative results about the structure, property and function of the mountain geocomplex. For determination the high mountain region on the mountains in the southwest part of the Republic of Macedonia (Jablanica, Galicica and Pelister) and for defining its low boundary are taken the following indicators: Pleistocene snow boundary, highness of the climate's and antropogen's up boundary of the forest belt and down boundary of appearance of the peryglacial relief forms.